A New Divergence Method for Heat Transfer with Neumann Boundary Condition - Sabri, Fatin Nabilah (Universiti Teknologi PETRONAS, 2017)
New Divergence Theorem is a new formulation for the simplest case of heat transfer problem involving Neumann Boundary Condition which combines two different numerical techniques which are Finite Element Method (FEM) and Finite Volume Method (FVM). The use of numerical techniques to solve such problems is therefore considered essentials since the powerful Finite Element Method (FEM) is capable in solving heat transfer analysis by giving a piecewise approximation of the domain. This study aims to evaluate the hypothesis of combining FEM with the FVM and to develop a new formulation of heat transfer problem involving Neumann Boundary Condition. Finite Volume Method (FVM), which uses the concept of Green Divergence Theorem, where a surface integral can be transformed to line integral has less accuracy since it develops the assumption of constant flux.